The internal determinants triggering corruption in Sabah Construction Industry. - Nur Muhammad, Dayang Noraini; Mohamed, Rozita @ Uji (Journal of Islamic, Social, Economics and Development, 2025)
orruption is like an endemic of problem in the construction industry which has been known for a long time, undeniably this global phenomenon eventually touched on issues of sensitivity to many parties. The construction industry plays an important role towards the country’s economic development as this influences investors to place their funds in this industry. It is found by many researchers as one of the most corrupt and riskiest sectors. Malaysian government and anti-corruption institutions have created ways to combat different corruption forms for construction industry. Corruption in the construction industry is not easy to be mitigate. Such of cases in Malaysia’s construction industry especially in Sabah for the year 2016-2022 notable the trends cases it is something to worry about. Hence, the main objective of this paper is to identify the most potential internal determinants that trigger corruption in the Sabah construction industry. Extensive literature review covers two independent variables i.e., cost project involvement and level of income as the internal determinants and corruption as the dependent variable. A conceptual framework deliberates the connection between these variables as discussed in the literature review. This paper contributes to the existing research providing knowledge on corruption specifically in Sabah.